Development of an Innovative Nitrite Sensing Platform Based on the Construction of an Electrochemical Composite Sensor of Polymer Coated CNTs and Decorated with Magnetite Nanoparticles. Issue 6 (19th March 2021) - Atta, Nada F.; Galal, Ahmed; Ahmed, Yousef M.; Abdelkader, Mohamed G.
Abstract: Electrochemical determination of nitrite in real water samples is achieved using simple and efficient electrochemical sensor. The sensor is fabricated by electrodeposition of a thin layer of poly(3, 4‐ethylenedioxythiophene) sandwiched by drop‐casting two thin layers of CNTs and iron oxide nanoparticles (Fe3 O4 ) over a GC electrode surface. Voltammetry determination of nitrite in tap water and wastewater samples in the concentration range (0.5–150 μM) is successfully achieved with detection limits of 22 and 24 nM, respectively. Practical application of the GC/CNT/PEDOT/Fe3 O4 sensor is efficiently assessed in real water samples for nitrite determination with acceptable recoveries, excellent anti‐interference ability and long‐term stability. Abstract :